Effect of Calcination at Synthesis of Mg-Al Hydrotalcite Using co-Precipitation Method - Niar Kurnia Julianti; Tantri Kusuma Wardani; Ignatius Gunardi; Achmad Roesyadi (The Journal of Pure and Applied Chemistry Research, 2017)
The use of hydrotalcite in catalysis has wide attention in academic research and industrial parties. Based on its utilization, hydrotalcite can be active catalyst or support. This research is focused on the investigation of characteristic like spesific surface area of Mg-Al hydrotalcite which is prepared with different temperature of calcination. Synthesis of Mg-Al hydrotalcites with Mg/Al molar ratio 3:1 were prepared by co-precipitation method. Mg(NO3)3.6H2O and Al(NO3)3.9H2O as precursors of Mg-Al hydrotalcite. Na2CO3 was used as precipitant agent and NaOH was used as buffer solution. The solution was mixed and aging for 5 hours at 650oC. The dried precipitate was calcined at 2500oC, 3500oC, 450oC, 550oC and 650oC. The characterization of functional group was determined by Fourier Transform Infra Red (FT-IR). The Identical peaks diffractogram were analyzed by X-Ray Diffraction (XRD). The spesific surface area was determined by adsorption-desorption of nitrogen. The largest surface area that obtained from the calcination temperature of 650oC is 156.252 m2/g.